Development of a Functional Biomarker for Use in Cell-Based Therapy Studies in Seropositive Rheumatoid Arthritis. (29th March 2016) - Shalev-Malul, Gali; Soler, David C.; Ting, Anthony E.; Lehman, Nicholas A.; Barnboym, Emma; McCormick, Thomas S.; Anthony, Donald D.; Lazarus, Hillard M.; Caplan, Arnold I.; Breitman, Maya; Singer, Nora G.
Abstract : This study tested the hypothesis that an ex vivo T-cell suppression assay could estimate response to novel cell-based therapy for rheumatoid arthritis (RA). Results showed multipotent adult progenitor cell products suppressed RA effector T cells. The study demonstrated the feasibility of using suppressor assays to detect biological effects of cell-based therapy in RA and suggests these effects are dose-dependent. Abstract: : Cell-based therapy has potential therapeutic value in autoimmune diseases such as rheumatoid arthritis (RA). In RA, reduction of disease activity has been associated with improvement in the function of regulatory T cells (Treg) and attenuated responses of proinflammatory effector T cells (Teff). Mesenchymal stem cells (MSCs) and related multipotent adult progenitor cells (MAPC) have strong anti-inflammatory and immunomodulatory properties and may be able to "reset" the immune system to a pre-RA state. MAPC are MSC-like cells that are slightly earlier in lineage, have greater expansion capacity, and can be used as "off-the-shelf" therapy. Assessment of cell-based therapy to treat arthritis and related diseases is limited by the lack of available biological correlates that can be measured early on and indicate treatment response. We set out to develop a functional measure that could be used ex vivo as a biomarker of response. We were able to demonstrate that MAPC products could inhibit Teff responses from patients with active RA and that Treg from RA patients suppressed Teff. This assay used ex vivo can be used with MAPC or Treg alone or in combination and reflects the overall level of Teff suppression. Use of a novel functional biomarker as an exploratory endpoint in trials of cell-based therapy should be of value to detect biological outcomes at a point prior to the time that clinical response might be observed. Significance: Therapy with mesenchymal stem cells and related multipotent adult progenitor cells is immune modifying in a variety of diseases. There is interest in using cell-based therapy in rheumatoid arthritis (RA) to induce tolerance and "reset" the immune system to its pre-RA state. In a clinical trial, it should be known as soon as possible if there is a chance of response. A biomarker has been developed that permits measurement of the effects of cell-based therapy on effector T cell function.